PERBANDINGAN KINERJA REKSA DANA SAHAM DAN REKSA DANA TERPROTEKSI DENGAN MENGGUNAKAN METODE SHARPE (Studi Pada Reksa Dana Saham dan Reksa Dana Terproteksi Yang Terdaftar Di Otoritas Jasa Keuangan Tahun 2015-2017) - Aulya Ramadhani ; Dr. Himmiyatul Amanah Jiwa Juwita, SE., MM
This research aims to determine the comparison of the performance of equity _x000D_ fund and protected fund and the method being used to measure the performance of_x000D_ mutual fund is sharpe method. The population in this reasearch consisting of all_x000D_ equity fund and non-sharia protected fund companies that has been registered in_x000D_ 2015 until 2017. Moreover, the sample are obtained by using purposive sampling_x000D_ method, therefore the sample consisting of 112 equity funds and 161 protected_x000D_ funds. This research used statistical analysis technique Mann-Whitney test. The_x000D_ result of this research shows that there is a significant difference between the_x000D_ performance of equity fund and protected funds by using Sharpe method. The_x000D_ implication in this research is directed to the investor to choose mutual fund_x000D_ investment using Sharpe method by taking the total risk into account. In addition_x000D_ the investment manager should consider appropriate budget allocation on the_x000D_ performance equity fund and protected fund._x000D_ _x000D_ Keyword: Equity Fund, Protected Fund, Sharpe Method.